Derazantinib (ARQ 087) in advanced or inoperable FGFR2 gene fusion-positive intrahepatic cholangiocarcinoma - Mazzaferro, Vincenzo; El-Rayes, Bassel F.; Droz dit Busset, Michele; Cotsoglou, Christian; Harris, William P.; Damjanov, Nevena; Masi, Gianluca; Rimassa, Lorenza; Personeni, Nicola; Braiteh, Fadi; Zagonel, Vittorina; Papadopoulos, Kyriakos P.; et al. (British journal of cancer, 2019)
Background Next-generation sequencing has identified actionable genetic aberrations in intrahepatic cholangiocarcinomas (iCCA), including the fibroblast growth factor receptor 2 (FGFR2) fusions. Derazantinib (ARQ 087), an orally bioavailable, multi-kinase inhibitor with potent pan-FGFR activity, has shown preliminary therapeutic activity against FGFR2 fusion-positive iCCA. Methods This multicentre, phase 1/2, open-label study enrolled adult patients with unresectable iCCA with FGFR2 fusion, who progressed, were intolerant or not eligible to first-line chemotherapy (NCT01752920). Subjects received derazantinib in continuous daily doses. Tumour response was assessed according to RECIST 1.1 every 8 weeks. Results Twenty-nine patients (18 women/11 men; median age, 58.7 years), 2 treatment-naive and 27 who progressed after at least one prior systemic therapy, were enrolled. Overall response rate was 20.7%, disease control rate was 82.8%. Estimated median progression-free survival was 5.7 months (95% CI: 4.04–9.2 months). Treatment-related adverse events (AE) were observed in 27 patients (93.1%, all grades), including asthenia/fatigue (69.0%), eye toxicity (41.4%), and hyperphosphatemia (75.9%). Grade ≥ 3 AEs occurred in 8 patients (27.6%). Conclusion Derazantinib demonstrated encouraging anti-tumour activity and a manageable safety profile in patients with advanced, unresectable iCCA with FGFR2 fusion who progressed after chemotherapy. A pivotal trial of derazantinib in iCCA is ongoing (NCT03230318).